‘Greening’ an oil exporting country: a hydrogen and helium closed-cycle gas turbines case study - Rawesat, Abdulwahab; Pilidis, Pericles (SCIE Publish, 2024)
Holistic decarbonisation requires collaborative efforts and substantial investments across diverse economic sectors. This study introduces an innovative national approach, blending technological insights and philosophical considerations to shape decarbonization policies and practices. Libya is the case study. The proposed framework involves submersible power stations with continuous-duty helium closed-cycle gas turbines to supply electricity demand and hydrogen. Extensive national data is analysed, incorporating factors such as sectoral consumption, sea temperature, and port locations. An analytical model is developed, providing a valuable foundation for realistic decarbonization scenarios. The model aims to maintain the benefits of current energy consumption, assuming a 2% growth rate, while assessing changes in a fully green economy. The results offer qualitative and quantitative insights on hydrogen use and an expected rise in electricity demand. Two scenarios are examined: self-sufficiency and replacing oil exports with hydrogen exports. This study provides a quantitative perspective on decarbonization, focusing on a submersible helium closed cycle gas turbine concept resistant to natural disasters and proliferation. Findings underscore the substantial changes and investments needed for this transition, identifying primary needs of 27 GW or 129 GW for self-sufficiency and exports, respectively. This foundational analysis marks the start of research, investment, and political agendas toward decarbonization.